2018
DOI: 10.2903/sp.efsa.2018.en-1410
|View full text |Cite
|
Sign up to set email alerts
|

Literature review and appraisal on alternative neurotoxicity testing methods

Abstract: The goal of this review was the evaluation of information on assessment methods in the field of alternative neurotoxicity (NT) testing. We therefore performed a systematic and comprehensive collection of scientific literature (in English) from the past 27 years until mid of 2017 on state of the art alternative testing methods including in vitro test methods, in silico methods and alternative non-mammalian models. This review identified a variety of test methods that have the ability to predict NT of chemicals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 125 publications
(107 reference statements)
0
27
0
Order By: Relevance
“…In a large study of about 900 chemicals, C. elegans was nearly as good at predicting developmental toxicity in rats or rabbits as those two species were at predicting each other ( Boyd et al, 2016 ). Additionally, the toxicodynamics and apical effects of many types of chemicals are similar in C. elegans and mammals, indicating that the C. elegans model has the potential to contribute useful information to human predictive integrated testing strategies ( Hartman et al, 2021 , Masjosthusmann et al, 2018 , Parish et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a large study of about 900 chemicals, C. elegans was nearly as good at predicting developmental toxicity in rats or rabbits as those two species were at predicting each other ( Boyd et al, 2016 ). Additionally, the toxicodynamics and apical effects of many types of chemicals are similar in C. elegans and mammals, indicating that the C. elegans model has the potential to contribute useful information to human predictive integrated testing strategies ( Hartman et al, 2021 , Masjosthusmann et al, 2018 , Parish et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A single C. elegans technician can assess a dozen or more compounds or concentrations in a week for endpoints such as viability, locomotor activity, developmental timing, or pathway of toxicity specific transgene expression. While this type of low-to-medium-throughput C. elegans screening cannot replace a descriptive toxicology study in lab mammals, it is very rapid and inexpensive by comparison, and can provide useful information on conserved modes of toxic action and apical endpoint responses ( Avila et al, 2020 , Hartman et al, 2021 , Masjosthusmann et al, 2018 , Parish et al, 2020 ). Several studies have demonstrated that toxicity ranking screens in C. elegans can predict developmental toxicity or LD50 ranking in mammals ( Boyd et al, 2010 , Boyd et al, 2016 , Hunt et al, 2012 , Li et al, 2013 ), indicating that C. elegans has the potential to provide a bridge between in vitro human cell based assays and mammalian in vivo oral toxicity testing ( Lagido et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The European Food Safety Agency (EFSA) is responsible for the registration of pesticides and all other substances that can contact or occur in food and are not assessed under REACH. Until now, the active compounds in pesticides need to be assessed for potential neurotoxic effects in mammals using the same rodent studies as under REACH (TG 424 and TG 426) only if it is indicative from their intended MoA or other information, like chemical structure, that the substance could be neurotoxic [23]. Neurotoxic effects on non-target species in the environment are not assessed.…”
Section: Current Role Of Eco-neurotoxicology In Risk Assessment For Rmentioning
confidence: 99%
“…This aspect was further verified by predicting a series of known neurotoxicants with the models predicting MIEs. The mode of action for these neurotoxicants was reported in a review by Masjosthusmann and coworkers [ 36 ] who gathered information from the literature about the targets upstream of the neurotoxicological pathway of these chemicals [ 11 , 12 , 37 ]. Interestingly, QSARs for the prediction of MIEs were able to identify the correct mode of action of several neurotoxicants.…”
Section: Discussionmentioning
confidence: 99%